2022
DOI: 10.1155/2022/9952118
|View full text |Cite
|
Sign up to set email alerts
|

Construction Accidents in Spain: Implications for an Aging Workforce

Abstract: Construction workers are getting older. In the European Union, the percentage of workers over 50 grew from 24.7% in 2011 to 31.5% in 2018, in Spain from 20.4% to 31.2%. Objective. Identify trends and detailed patterns of accidents of older construction workers compared to other age groups. Data and Method. We analyzed construction accidents in Spain from 2011 to 2018 ( N = 455,491 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The results of this study (2012-2021) showed that crane operators working for micro-companies suffered 27.7% of all crane-related accidents, those working for small companies suffered 43.92% and those belonging to medium-sized companies accounted for 23.44% of the total reported cases. These data were in agreement with those of Camino-López et al [39] and Fontaneda et al [50], both related to the Spanish construction industry. The analysis of the relationship between the size of the company and the rate of crane-related occupational accidents evidences an important, largely neglected risk factor of psychological nature; namely, operating a crane is more sophisticated and mentally demanding than operating other equipment; therefore, crane operators may be more vulnerable to human error [62].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study (2012-2021) showed that crane operators working for micro-companies suffered 27.7% of all crane-related accidents, those working for small companies suffered 43.92% and those belonging to medium-sized companies accounted for 23.44% of the total reported cases. These data were in agreement with those of Camino-López et al [39] and Fontaneda et al [50], both related to the Spanish construction industry. The analysis of the relationship between the size of the company and the rate of crane-related occupational accidents evidences an important, largely neglected risk factor of psychological nature; namely, operating a crane is more sophisticated and mentally demanding than operating other equipment; therefore, crane operators may be more vulnerable to human error [62].…”
Section: Discussionsupporting
confidence: 93%
“…However, few published studies have used this variable in the analysis of occupational accidents in the construction industry. Among them, Camino-López et al [39] analyzed a total of 1,630,452 accidents suffered by construction workers in Spain between 1990 and 2000; Betsis et al [49] analyzed a sample of 413 notified construction accidents that occurred in the north of Greece between 2003 and 2007; and finally, Fontaneda et al (2022) [50] analyzed 455,491 construction accidents in Spain notified between 2011 and 2018. Only the mentioned study by Camino-López et al [39] included "cranes and lifting equipment" among the analyzed material agents.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, FFH is the leading cause of fatal injuries in construction workers [20]. Along with an aging society, the average age of construction workers is also increasing [21,22]. According to the US Bureau of Labor Statistics, the average age of construction workers in 2022 was 42.5 years [23].…”
Section: Differences Between Jumpers and Fallersmentioning
confidence: 99%
“…Older construction workers are generally more prone to work-related injuries. Indeed, physical decline, reduced coordination, and slow reaction times can increase the chances of accidents, musculoskeletal injuries, and falls in older construction workers [22]. Safety education, use of protective equipment, and compliance with safety guidelines should be conducted considering the increasing age of construction workers [25,26].…”
Section: Differences Between Jumpers and Fallersmentioning
confidence: 99%
“…A safe workplace setting is important for workers' productivity [3][4][5], and a clean environment is associated with no risk of bumping into objects [6]. Additionally, working at surface level is associated with no risk of falling from height [7].…”
Section: Introduction 1background Of the Studymentioning
confidence: 99%